PENDIDIKAN MULTIKULTURAL SEBAGAI ALTERNATIF PENANAMAN NILAI MORAL DALAM KEBERAGAMAN - Rosita Endang Kusmaryani (Paradigma, 2006)
One of the relevant issues to current condition is the diversity in society. This is the result of mobility and information stream which develops more and more rapidly. Foreign cultural values flow into thesociety, following the stream and give positive as well as negativeimpacts.This condition of diversity is often assumed as a threat for the unity of nation and state. Oftentimes, certain rules and regulations made as theresponds to the diversity turn out to be a facility for the majority culture to dominate. The slogan of “Bhinneka Tunggal Ika” (unity in diversity) as aninheritance of the New Order era constitutes the case which shows howmulti-cultures was incorrectly managed by disregarding multiculturalismitself. An assumption that diversity will endanger the wholeness of ournation becomes the reason to force the diversity be kept in an integrityand unity, which eventually leads to the existence of monoculturalism.Domination of the majority culture, the legacy from incorrect perceptionand management of Bhinneka Tunggal Ika in the past gives impact tovarious aspects of life in the present Indonesian society. The lack ofcomprehensive understanding for multiculturalism even causes moraldecadence of the young generation. Such merits as togetherness, appreciation and respect to others, and mutual cooperation arevanishing. The arrogance due to domination of majority culture causeslack of understanding in interactions with other cultures or other people.This condition turns to become a challenge for education milieu to givemore orientation to multicultural understanding. Schools, through theteaching-learning process, need to emphasize that diversity is a potentialwealth and worth understanding, and should not be considered anegative aspect. Multicultural education is expected to be the solution forthe problems of national moral degradation.Key words: diversity, multiculturalism, majority culture